Simulating SPH Fluid with Multi-Level Vorticity - Jang, Taekwon; Blanco i Ribera, Roger; Bae, Jinhyuk; Noh, Junyong (International Journal of Virtual Reality, 2011)
The vortical motion of fluid in various scales is one of the most important elements in capturing the vivid realism of turbulent water. However, it is still challenging to resolve mul-ti-level vorticity effectively. This paper presents a novel hybrid method that combines a smoothed particle hydrodynamics (SPH) system with multiple Eulerian grids to reproduce the multi-level vorticity. In our hybrid method, the SPH system is responsible for resolving flow velocity while the multiple grids support the SPH system in efficiently detecting and computing the multi-level vor-ticity field.